Hooked Pins in the Przeworsk Culture – Typology, Chronology, Distribution and Function - Stącel, Wojciech (the Authors, 2021)
Thanks to the analysis of hooked pins in the Przeworsk culture, a new division of this category was introduced. A new typological classification of the hooked pins was made and their two types (1–2) and their subtypes (A–B) were defined. The article takes into account the territorial and chronological range of their occurrence, from the early Pre-Roman Period to Roman Period and the Migration Period. The function of the hooked pins is also presented.
Keywords: metal tools; pins; spinning; Przeworsk culture